PEMBANGUNAN HUKUM ARBITRASE DI BIDANG KONSTRUKSI (Politik Hukum) SEBAGAI UPAYA PENYELESAIAN SENGKETA (Tinjauan atas Undang-Undang No. 30 Tahun 1999 Tentang Arbitrase dan Alternatif Penyelesaian Sengketa Dan Tinjauan Atas Undang-Undang Nomor 2 Tahun 2017 Tentang Jasa Konstruksi) - Annisa Mayangsari; Agoes Ary Prasetio; Rildo Rafael Bonauli (Universitas Muhammadiyah Jember, 2020)
AbstractIn the current Government era where the Construction service industry has developed rapidly with all-round technology, the problem of claims is well known and is a common problem between Service Users and Service Providers in the Implementation of Construction Projects. Service Providers compete to win job tenders. Almost all service providers master technology and the ins and outs of construction services so that the price difference offered by the Service Provider at the time of the tender is no longer related to the difference in the price of goods and wages for a job but they are competing in their work efficiency. Construction service companies look for opportunities to win tenders not in terms of efficiency but in their prudence to see large claims opportunities at the time of the tender. Indonesia has interpreted the claim as a claim / lawsuit, so that the claim is not handled and served well but treated as something scary, therefore the government issued regulations that can regulate dispute resolution. The formation of arbitration is an interesting study of legal politics, given that its application is still an effective and professional problem so that the principles of justice and equality as mandated by Law No. 18/1999. This study requires two studies, namely one, how is the Indonesian Legal Dispute Resolution in arbitration? Second, what is the political understanding of arbitration law and what is its purpose. This study uses normative legal research methods which include research on legal principles. This study basically uses a qualitative method that examines the concept of the legal concept of political arbitration in its formation (legal politics). With the aim of providing an overview of the development of law in Indonesia, especially in the context of arbitration law. The results of this study note that the development of economic law, especially in the regulation of arbitration law tends not to start from the values that exist in society, but is taken from an urgent need at the time of reform even though it is in line with the development of law in the process of legal reform for justice and welfare law for the community, especially for entrepreneurs and business actor.